PRAKTEK KAWIN MUT’AH DI INDONESIA DALAM TINJAUAN HUKUM ISLAM DAN UNDANG-UNDANG PERKAWINAN - Isnawati Rais (AHKAM : Jurnal Ilmu Syariah, 2014)
The Practice of Mut’ah Marriages in Indonesia in the Review of Islamic Law and the Law of Marriage. Mut’ah marriage is marriage performed by a certain time limit which in Indonesia known as the marriage contract. Sunni Muslim tend to forbid the practice of mut’ah marriage while Syi’ah allow it. The practice of mut’ah marriage has been rife in some areas in Indonesia where the Sunni is majority so many people who protest and regard it as deviant behavior or forbidden. Laws marriage prohibits the practice of mut’ah marriage as Law Number 4 of 1974 and Government Regulation Number 9 of 1975 although there is a part of society who gives a different interpretation of the legislation.DOI: 10.15408/ajis.v14i1.1246